PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 52 PARUPUK TABING KOTA PADANG - Dzakiya Zahra Fadhila; Yesi Anita; Rafhi Febryan Putera; Hana Shilfia Iraqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the improvement of students' learning outcomes in Pancasila Education learning using the Problem-Based Learning model in Class V of SDN 52 Parupuk Tabing, Padang City. This research is a Classroom Action Research (PTK) that employs both qualitative and quantitative approaches. The study was conducted in two cycles, cycle I consisted of two meetings, and cycle II consisted of one meeting. The research subjects were the teacher (researcher) and 20 students, consisting of 9 male and 11 female students. The results of the study showed improvements in: (1) The average score of the teaching module planning in cycle I was 87.51% (Good), which increased to 95.83% (Very Good) in cycle II; (2) The average teacher activity implementation score in cycle I was 83.9% (Good), which increased to 96.4% (Very Good) in cycle II; (3) The assessment of students’ learning outcomes in cycle I had an average score of 73.5% (Fair), which improved to 93.2% (Very Good) in cycle II.